Financing Smart Tourism: Investment Trends in Digital Infrastructure for Tourist Destinations in India - Ankita Chourasia (AG Volumes, 2026)
India’s tourism sector is undergoing a transformation as digital infrastructure becomes central to destination development. Smart tourism—driven by technologies such as AI, IoT, mobile applications, and big data—presents opportunities to enhance visitor experience, improve governance, and boost sustainability. However, financing the digital backbone of smart destinations remains a significant challenge. This paper explores investment trends, public and private financing mechanisms, and digital infrastructure development for tourist destinations across India. Through analysis of government programs, PPP models, and case studies from cities like Varanasi, Hampi, and Jaipur, the research highlights the growing momentum toward digitized tourism and the need for strategic financial planning to scale such initiatives across urban and rural India.